Uma análise construtivista do voluntariado corporativo em ações educativas com utilização de mídias na escola - Prado, Marthina Endo do (2016)
The volunteer work programs have been drawing attention inside organizations, mainly, because of the benefits it brings for all the sides involved, the company, the community and the employees. It can also be noted by analyzing the collected data in 2012, by the Brazilian Business Volunteering Council, the educational field is the one that receives the most financial assistance from these programs. Therefore trying to fully understand the corporate volunteering in a constructivist perspective, this research intends to analyze the educational volunteering actions devised by a Corporate Volunteering Program (CVP), using medias in the learning process. The methodology used for the research was qualitative and exploratory. In order to obtain data a questionnaire with subjective and objective questions was applied to the volunteers who participated in the CVP actions that used medias during the year of 2015. The results were analyzed by categories, regarding the activities performed by this volunteers in the school and in the company. Also an evaluation was performed in the profile of such volunteers, considering specially level of formal education and gender, this evaluation showed that, in its majority the volunteers in this programs have a high level of education and are women. Concerning the volunteering activities, data analysis was based in the constructive principles created by Jonassen, and in the collaborative learning fundamentals created by Jonhson and Jonhson, concerning the following aspects: collaboration, problem solving and the intentionality in learning; objectives and reflection about learning. In an educational perspective, it was concluded that such activities design in their theoretical conception have constructivist and collaborative characteristics, however there is a distance between project fundamentals and volunteering practice. Also it was identified a need to properly train volunteers for the educational practice. Concerning the company, the research shows that, generally, volunteers consider the collaboration as extremely important inside the organization.